Plutarch’s Boat : On the spiritual sense of the scenic interruption - Kirkkopelto, Esa (Taylor & Francis, 2022)
The article considers how the scene in the scenic presentation can constitute a twofold instance of interruption—not only as an intervening element within a performance but also as something that may interrupt it entirely—and how these two interruptions are intertwined. The demonstration builds on a scenic lecture of the classical text by Plutarch on the disappearance of oracles, dating from the first century CE. The text is renowned for its story of the death of ‘the Great Pan’. A closer analysis of the text indicates how that seemingly eccentric story is essentially motivated by the worry of the author concerning the disappearance of ‘providence’ and thereby the sense of ‘allness’ (pan) provided by a historical world. The conclusion links the story to the present-day post-pandemic situation: What if, on every occasion when a human community or society, a dêmos or ‘people’, becomes interrupted by its fundamental exposedness to the disastrous effects of the non-human universe, no matter what is their cause, a certain ‘allness’ dies? What are the spiritual, political and transcendental consequences of that event in history, and what are they today? Insofar as these questions can only open in a scenic perspective, they re-articulate the scene or the stage, in a novel way, as a dimension of radical exposure engaging our experience and bodies genuinely and relating them to what they are not.
Keywords: teatteritaide; esitykset; pandemiat; näytelmät; filosofia; näytelmäkirjallisuus; metafysiikka